HUBUNGAN PENGETAHUAN DENGAN STIGMA TOKOH AGAMA TERHADAP ORANG DENGAN HIV/AIDS DI KABUPATEN BANYUMAS - Retnowati, Misrina (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Theincreasingly alarming rate of HIV/AIDS spread, requires an integrated response fromshareholders, both government, non-governmental organizations, including religiousleaders. Religious leaders are believed to play a strategic role in overcoming adverseimpacts, as well as breaking the link between HIV and AIDS. These include providingunderstanding to religious communities, there by reducing stigma and discriminationagainst people living with HIV. The objective of the study was to describe the knowledgeand stigma of religion towards people with HIV/AIDS. Know the relationship ofknowledge with the stigma of religion towards people with HIV/AIDS. The researchmethod is correlational analytic research with cross sectional approach. The populationis all religious leaders in Banyumas Regency with 278 people, with a sample of 164people taken proportional random sampling. The results of the study most of therespondents have less knowledge about HIV/AIDS as much as 59.1%. There is arelationship of knowledge with stigma of religion towards people with HIV/AIDS with Ïvalue 0.000. Conclusion there is a relationship of knowledge with stigma of religiontowards people with HIV/AIDS.Keywords: Knowledge, Stigma of Religion towards People with HIV/AIDS